The application of genetic algorithm to solve unit commitment problem/ Zuhairi Baharudin - Baharudin, Zuhairi (1998)
Unit Commitment problems are well known in the power industry and have the potential to save millions of money per year in fuel and related costs. It is an area of production scheduling that relates to the determination of the on/off status of the generating units during each interval of the scheduling period. In this thesis proposes an innovative Genetic Algorithm (GA) approach to solve the thermal unit commitment (UC) problem in power generation industry. Due to large variety of constraints to be satisfied a proper fitness function of the GA is built. MATLAB program is used to solve the unit commitment problems and to represent the fitness function of die GA.